Greg is solving a polynomial equation and gets stuck at this step: x^2(2x−1)+5x(2x−1)+4(2x−1) Which of the following is a solution? (Select all that apply) (3 points)

1. -1
2. -4
3. 1
4. 1/2
5. 0

1 answer

To find the solutions of the polynomial equation, we can factor out the common factor of (2x-1):

x^2(2x-1) + 5x(2x-1) + 4(2x-1)

= (2x-1)(x^2 + 5x + 4)

Now, we need to find the values of x that make the expression (2x-1)(x^2 + 5x + 4) equal to zero. Thus, the solutions are the values of x that make either (2x-1) or (x^2 + 5x + 4) equal to zero.

To solve for (2x-1) = 0, we get:
2x-1 = 0
2x = 1
x = 1/2

To solve for (x^2 + 5x + 4) = 0, we can factor the quadratic expression:
(x+4)(x+1) = 0
x+4 = 0 or x+1 = 0
x = -4 or x = -1

Therefore, the solutions to the polynomial equation are:
1. x = 1/2
2. x = -4
3. x = -1

So, the correct answers are 1, 2, and 3.